Analyzing Gender Disparities in the Labour Market in an Urbanizing City- Maseru, Lesotho - Keneuoe Anacletta Mots’oene (Journal of Social and Development Sciences, 2017)
The study aimed at investigating the gender differences in the labour market of the urban formal sector in Maseru. The research was undertaken to illustrate the existing gender gap between men and women both in occupation and remuneration thus exposing inequality manifestations particularly in an urbanizing city, Maseru. The assessment was carried out in Maseru urban formal sector in three government entities: the National Manpower Development Secretariat, Office of the Auditor General and Ministry of Labour. The three government entities were purposively selected because of easy access of documented data and availability of resource persons to assist during data collection exercise. While at the same time a few interviews were conducted with men working in the taxi industry and the informal sector. Observations as well formed part of approach to the study to ascertain the validity of information obtained from the documented data and interviews. The main finding of the paper is that women in Lesotho the paper concludes that the formal labour market in Maseru is characterized by gender gaps where women occupy well salaried positions as opposed to their male counterparts with these low income jobs thus making men live in vicious cycle of poverty.